1990
DOI: 10.1016/0140-1971(90)90039-a
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between family structure and process variables and adolescent decision making

Abstract: This study examined the relationship between family structural and process variables and adolescent participation in family decisions and vigilant decision making. Data were obtained from a survey sample of 585 adolescents aged 12–18 years living in Adelaide, South Australia. Adolescents from one‐parent families participated in a greater number of family decisions than those from two‐parent families. Adolescents from families adaptable in allocating roles and setting rules participated in more family decisions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 10 publications
4
33
0
1
Order By: Relevance
“…Studies often have revealed opposite conclusions, as well as complicated interactions between parents ' and adolescents ' gender, as suggested above. Studies have indicated, for example, that mother -daughter relationships become particularly disrupted and conflictual during adolescence (Buchanan et al, 1990 ;Holmbeck & Hill, 1991 ;Montemayor, 1982Montemayor, , 1986Smetana, 1988aSmetana, , 1989Smetana, Daddis, & Chuang, 2003 ), although other research has not supported this pattern (Hill & Holmbeck, 1986 ;Smetana, Yau, & Hanson, 1991 ;Papini et al, 1988 evidence that adolescent girls perceive higher levels of autonomy support from parents, and are granted more input into family decision making (Beyers & Goossens, 1999 ;Brown & Mann, 1990 ;Flanagan, 1990 ;Fuligni & Eccles, 1993 ;Holmbeck & O ' Donnell, 1991 ;Jacobs, Bennett, & Flanagan, 1993;Soenens et al, 2007 ). However, these differences may at least partially depend on the gender of the parent and on other family characteristics, such as cultural context and parental attitudes toward gender roles (Bumpus, Crouter, & McHale, 1998 ;Daddis & Smetana, 2005 ).…”
Section: Attachment Autonomy and Gendermentioning
confidence: 94%
“…Studies often have revealed opposite conclusions, as well as complicated interactions between parents ' and adolescents ' gender, as suggested above. Studies have indicated, for example, that mother -daughter relationships become particularly disrupted and conflictual during adolescence (Buchanan et al, 1990 ;Holmbeck & Hill, 1991 ;Montemayor, 1982Montemayor, , 1986Smetana, 1988aSmetana, , 1989Smetana, Daddis, & Chuang, 2003 ), although other research has not supported this pattern (Hill & Holmbeck, 1986 ;Smetana, Yau, & Hanson, 1991 ;Papini et al, 1988 evidence that adolescent girls perceive higher levels of autonomy support from parents, and are granted more input into family decision making (Beyers & Goossens, 1999 ;Brown & Mann, 1990 ;Flanagan, 1990 ;Fuligni & Eccles, 1993 ;Holmbeck & O ' Donnell, 1991 ;Jacobs, Bennett, & Flanagan, 1993;Soenens et al, 2007 ). However, these differences may at least partially depend on the gender of the parent and on other family characteristics, such as cultural context and parental attitudes toward gender roles (Bumpus, Crouter, & McHale, 1998 ;Daddis & Smetana, 2005 ).…”
Section: Attachment Autonomy and Gendermentioning
confidence: 94%
“…What is unique about the current situation is that there appears to be fewer legal barriers to the increased complexity and it is occurring on a global scale (Maclean & Eekelaar, 1997). There has been a well-documented decline in the 'intact' or 'traditional' family household (Haskey, 1998) and consequently, step-families (or blended families as described by Brown and Mann, 1990) formed as a result of individuals re-marrying or co-habiting with new partners are more prevalent than single parent households.…”
Section: Changes In the Family Unitmentioning
confidence: 99%
“…The primary decision making style is considered as being the dominant decision making style, being the most prevalent when making decisions. Brown and Mann (1990) and Udell et al (2008) emphasize the importance that the familial environment plays in the development of adolescent decision making abilities. In addition, the way in which adolescents develop their decision making is often based on their parents' decision making strategies (Ö zȕtrk et al 2011).…”
Section: Parenting Approaches and The Relationship With Child And Adomentioning
confidence: 99%